Empowering Digital Citizenship in Indonesia: Navigating Urgent Digital Literacy Challenges for Effective Digital Governance - Isabella, Isabella; Alfitri, Alfitri; Saptawan, Ardiyan; Nengyanti, Nengyanti; Baharuddin, Tawakkal (Universitas Muhammadiyah Yogyakarta, 2024)
Currently, the level of digital literacy in Indonesia still needs to be improved. In the ever-growing digital era, digital literacy is a critical skill and knowledge for society. This research aims to explore the literacy policies implemented and the challenges faced by the government in supporting increased literacy in digital governance in Indonesia. This study uses a qualitative approach using Online Research Methods (ORMs) as a data collection method. The analysis tool that is maximized is Nvivo 12 Plus. The findings of this research show that digital literacy plays an essential role in ensuring the active participation of citizens in governance, efficiency of public services, growth of the digital economy, and security in the digital environment. Strong digital literacy is essential for Indonesian society because it allows better access to online services and bridges the public into an era of ever-growing digital democratization. This condition could make Indonesia ready and adaptive to the progress of the digital era. However, the implementation of digital literacy policies is also faced with several inhibiting factors, such as disparities in access and infrastructure, economic and social challenges, lack of education and training, lack of research and data, lack of involvement and coordination between parties, rapid technological changes, including the framework regulations that are not yet fully accommodating. Therefore, Indonesia needs adaptive policies to overcome these obstacles so that digital literacy can increase evenly.